2012
DOI: 10.1016/j.psyneuen.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Decreased hydrocortisone sensitivity of T cell function in multiple sclerosis-associated major depression

Abstract: Summary Multiple sclerosis (MS) is an inflammatory, demyelinating disease of the CNS with a high prevalence of depression. Both MS and depression have been linked to elevated cortisol levels and inflammation, indicating disturbed endocrine-immune regulation. An imbalance in mineralocorticoid versus glucocorticoid signaling in the CNS has been proposed as a pathogenetic mechanism of depression. Intriguingly, both receptors are also expressed in lymphocytes, but their role for 'escape' of the immune system from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…For example, impaired suppression of T-cell proliferation by dexamethasone was prospectively associated with greater depressive symptoms in deployed military personnel (van Zuiden et al, 2012) and multiple sclerosis patients (Fischer et al, 2012). However, the findings of TNF production in relation to GC sensitivity are limited; to our knowledge, no other reports are currently available in which intracellular monocytic TNF was measured under cortisol treatment to directly investigate cellular responses in a well-defined monocytic population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, impaired suppression of T-cell proliferation by dexamethasone was prospectively associated with greater depressive symptoms in deployed military personnel (van Zuiden et al, 2012) and multiple sclerosis patients (Fischer et al, 2012). However, the findings of TNF production in relation to GC sensitivity are limited; to our knowledge, no other reports are currently available in which intracellular monocytic TNF was measured under cortisol treatment to directly investigate cellular responses in a well-defined monocytic population.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of depression in populations with these different diseases is much higher (up to 30% or even higher) than that of the general population, which is 10.3%. (Bachen et al, 2009; Besnard et al, 2011; Cafarella et al, 2012; Duewell et al, 2010; Eisner et al, 2005; Evans et al, 2005; Fischer et al, 2012; Gasse et al, 2009; Gris et al, 2010; Halle et al, 2008; Kastbom et al, 2008; Kessler et al, 1994; Mason et al, 2012; Mitroulis et al, 2010; Nery et al, 2007; Pontillo et al, 2012; Sheehy et al, 2006; Shin et al, 2012; Vandanmagsar et al, 2011; Wen et al, 2011; Zhou et al, 2010). …”
Section: Figmentioning
confidence: 99%
“…The inhibitory concentration 50 (IC-50) values representing concentrations inhibiting 50% of the PHA-induced proliferation for each subject and agonist were determined by nonlinear sigmoidal curve fitting utilizing Prism® Software as described by Fischer et al (2012). All variables were tested for normality and equality of variance.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that GC sensitivity of T cell function is unaltered in BDP, which may indicate a tissue-specific dysregulation of steroid signaling. In vitro inhibition of cell proliferation has previously been used to reveal differences in GC sensitivity of T cells as a biological substrate of depressive symptoms in patients with multiple sclerosis, a neuroinflammtory disease of presumably T cell-driven origin (Fischer et al, 2012). Similarly, studies have shown altered GC sensitivity of T cell proliferation in patients with PTSD (de Kloet et al, 2007) and major depression (Lowy, Reder, Gormley, & Meltzer, 1988;Wodarz et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation